(3GdJfejI GdEbJUGOjI heTcdGJgG (B:s (3eTGcd GdabQ(B-(3GdJdhK GdHjFj(B-(3GdJfejI GdeSJOjeI (B/s - (3YLejI, eMeO YHO GdYRjRs; (3fLG, Ydj YHO GdhgGH s ((3GdEScfOQjI(B: s (3OGQ GdJYdje GdLGeYj(B, s, 2013)
(3eTcdI bjGS Gdfeh GdEbJUGOj hGdJfejI GdEbJUGOjI(B- (3eTcdI GdHWGdI aj eUQ(B- (3GdYhdeI hCKQgG Ydi Gdfeh GdEbJUGOj aj eUQ(B- (3GdJZjQGJ aj JhRjY GdONd aj eUQ NdGd aJQI GdEUdGM GdEbJUGOj OQGSI JMdjdjI(B- (3eTcdI GdabQ hhGbYgG aj eUQ(B- (3eTcdI GdJdhK GdHjFj hGdJfejI GdeSJOjeIs
Keywords: (3GdJfejI GdEbJUGOjIs; (3eTGcd GdJfejIs; (3eTcdGJ GLJeGYjIs